Incomeenvironmental nexus in Africa: The integrating role of renewable energy transition and governance quality - Iorember P.T.; Yusoff N.Y.M. (John Wiley and Sons Inc, 2024)
The economies of the African countries are gradually expanding, but they mostly depend on fossil fuels for energy use. This exacerbates environmental damage, which renders the continent susceptible to the effects of climate change. Therefore, this study aims to examine the integrating role of renewable energy transition and governance quality in the incomeenvironmental quality nexus in Africa. The study applies second-generation econometric techniques on annual panel data of 34 African countries covering the period 19962018. The fixed effect ordinary least square (OLS-FE), feasible generalized least squares (FGLS), system generalized method of moments (SYS-GMM) and cross-sectionally augmented ARDL (CS-ARDL) are applied to both the baseline model and the interactive models. The results provide diverse findings. In the baseline models, the study verifies the increasing effect of income on carbon dioxide (CO2) emissions, which continues to dampen environmental quality. Regarding the interaction effect models, the findings show that the interactive term of renewable energy transition and income per capita has a significant negative effect on CO2 emission levels which implies that renewable energy transition ensures green growth. Further, the results indicate that the interactive terms of governance quality have significant reducing effect on emission levels. In terms of policy, achieving green growth necessitates increased renewable energy deployment and policies that will enhance governance effectiveness towards enforcing environmental regulations. 2023 African Development Bank (AFD).